Chapter L'estensione del dominio dell'amicizia. Signori e amici in Lombardia e Italia centro-settentrionale, secoli XIV-XV - Del Tredici, Federico (Reti Medievali E-Book, 2021)
At the end of the Middle Ages in Lombardy it was common for a rural lord and his subjects to be defined as friends. By comparing Lombardy to other areas of central and northern Italy, the essay underlines the exceptional nature of this situation, and questions its causes. Such a phenomenon had two main underlying reasons: on the one hand, the peculiar political relationship between city and countryside that distinguished Lombardy since the late thirteenth century; on the other hand, the strong consensual character of the Lombard lordship in the fourteenth and fifteenth centuries.